Network analysis and in vivo experiments reveal the therapeutic mechanisms of total ginsenosides in a Drosophila model of ulcerative colitis - He, Gongchen; Sun, Jian; Gu, Yuexin; Zheng, Yanjie; Wang, Liang; Sun, Yanyan (Frontiers in Pharmacology, 2025)
Gut homeostasis is critical for human health, ulcerative colitis (UC) can disrupt gut homeostasis and cause disease. Panax ginseng C.A. Meyer is a widely used traditional herbal medicine known for its anti-inflammatory, antioxidant, and immunomodulatory effects. However, the protective mechanisms of total ginsenosides (TG) in treating UC remain unclear. In this study, we employed Drosophila melanogaster as a model organism to investigate the protective effects of TG on dextran sulfate sodium (DSS)-induced intestinal injury. Our data showed that TG significantly improved survival rates in female flies, restored intestinal length, maintained intestinal barrier integrity, and alleviated oxidative stress. Additionally, TG may protect against intestinal damage by activating the PI3K/Akt signaling pathway and inhibiting the JAK/STAT signaling pathway. These findings suggest that TG alleviates UC symptoms through multi-target regulation, highlighting its potential for developing novel therapeutic strategies for UC.